Constructing Digital Selves: A Narrative Review on Identity in Online Communities - Putra, M. Nuur Tanja (Communica : Journal of Communication, 2024)
In the digital era, identity construction has become increasingly intertwined with online interactions and platform-based communication. This narrative review aims to synthesize contemporary findings on how individuals construct and express identities within diverse online communities. Utilizing qualitative and quantitative studies retrieved from Scopus, PubMed, and Google Scholar, the review focuses on four primary contexts: social media platforms, online activism, role-playing games, and professional networking sites. Keywords such as "identity construction," "online communities," and "digital communication" guided the search and selection criteria. Findings reveal that identity is constructed through a range of communicative and narrative practices, including visual content creation, emotive expression, and community engagement. In social media, users employ multimodal strategies to project curated personas; in activist forums, shared narratives and symbols reinforce collective identities. Role-playing environments allow for creative exploration of identity via avatars and storylines, while professional platforms emphasize self-curation aligned with career aspirations. These processes are deeply influenced by systemic factors such as platform algorithms, socio-economic access disparities, and cultural norms. This review highlights the need for inclusive digital policies and educational initiatives to counteract algorithmic bias and bridge digital divides. Moreover, it calls for future research focusing on marginalized groups and non-Western perspectives to deepen global understanding. Overall, this study contributes to the growing scholarship on digital identity and offers practical insights for fostering equitable online engagement.